Management of a Rare Case of Geminated and Fused Central Incisors in the Same Maxillary Dental Arch - Anas Alyahya; Humam Karkoutly; Hussam Milly (Case Reports in Dentistry)
A 27-year-old man presented with developmental disorders in the maxillary incisors and asymmetric smile. Differential diagnosis between geminated and fused maxillary central incisors was conducted using cone-beam computed tomography (CBCT). The complexities of root canal system was handled using suitable shaping instruments and ultrasonic activation tips. Root apexes were sealed with mineral trioxide aggregate plugs. The anterior maxillary gingiva was surgically recontoured, and CAD/CAM Zirconia crowns were placed after the gingival healing phase. The combination of the 3D radiological examination, the clinical screening, and the use of a diagnostic wax-up presented a successful approach to manage this rare clinical case.